Celecoxib in Cancer Therapy and Prevention – Review - Tołoczko-Iwaniuk, Natalia; Dziemiańczyk-Pakieła, Dorota; Nowaszewska, Beata K.; Celińska-Janowicz, Katarzyna; Miltyk, Wojciech (Current Drug Targets, 2019)
Background and Objectives: It is generally accepted that inflammatory cells found in the tumor microenvironment are involved in the neoplastic process, promoting cell proliferation, survival, and migration. Therefore, administering anti-inflammatory medication in cancer therapy seems to be justified. A potential pathway associated with the aforementioned issue is cyclooxygenase-2 inhibition, particularly as the overexpression of this enzyme has been proven to occur in cancer tissues and is also associated with a poor prognosis in several types of human malignancies. Celecoxib, a COX-2 selective inhibitor, has been utilized for over 20 years, particularly as an anti-inflammatory, analgesic and antipyretic medication. However, to date, its antineoplastic properties have not been sufficiently investigated. In recent years, the number of research studies on the antineoplastic effects of celecoxib has increased considerably. The vast majority of publications refers to preclinical studies attempting to elucidate its mechanisms of action. Clinical trials concerning celecoxib have focused primarily on the treatment of cancers of the colon, breast, lung, prostate, stomach, head and neck, as well as premalignant lesions such as familial adenoma polyposis. In this review article authors attempt to summarise the latest research which has elucidated celecoxib use in the treatment and prevention of cancer. Conclusion: Both preclinical and clinical studies have demonstrated promising results of the role of celecoxib in the treatment and prevention of cancer – the best outcome was observed in colon, breast, prostate and head and neck cancers. However, more clinical trials providing real evidence-based clinical advances of celecoxib use are needed.
Keywords: Cancer